Metazoan Parasites of Perch Perca fluviatilis L. From Lake Sigirci, Ipsala, Turkey - (:unkn) unknown (ZOOLOGICAL SOC PAKISTAN, 2013)
There has been no previous parasitological survey of perch Perca fluviatilis in Turkey. Consequently, the objectives of the present study were to investigate the metazoan parasite communities of perch and also to calculate infection parameters of the parasites in a eutrophic lake. A total of 52 perch were collected seasonally from Lake Sigirci in Ipsala, Turkey, between April 2009 and February 2010. Perca fluviatilis specimens were parasitized by eight species. The parasite prevalence and mean intensity (MI), respectively, for the whole material were: Gyrodactylus sp., 5.8%, MI (+/- SD) 2.6 +/- 0.57; Displostomum sp., 71.1%, MI 6.2 +/- 4.64; Tylodelphys clavata, 98.1%, MI 175.7 +/- 62.64; Tetracotyle sp., 3.9%, MI 1.5 +/- 0.70; Clinostomum complanatum, 15.4%, MI 3.5 +/- 4.40; Proteocephalus percae, 55.7%, MI 47.10 +/- 55.67; Eustrongylides excisus, 94.2%, MI 42.2 +/- 62.89; Glochidium sp., 30.8%, MI 23.5 +/- 27.42. From the current results it can be concluded that, in perch from Lake Sigirci, T clavata, E. excisus, Diplostomum sp. and P. percae are the most prevalent parasite species.
Keywords: Metazoan parasites; perch; Lake Sigirci; Turkey; PROTEOCEPHALUS; DIPLOSTOMUM; INFECTION; FISH